HUBUNGAN INDEKS MASSA TUBUH DENGAN DERAJAT KEPARAHAN OSTEOARTHRITIS LUTUT DARI FOTO POLOS MENURUT KELLGREN-LAWRENCE GRADING SCALE DI RUMAH SAKIT SITI KHODIJAH MUHAMMADIYAH CABANG SEPANJANG - Muslim Andala Putra; Bella Auliya Puspita Ningrum; Laily Irfana; Nur Mujaddidah Mochtar (Universitas Muhammadiyah Surabaya, 2023)
Osteoarthritis is a disorder that attacks the cartilage of the joints so that they are thinned and sometimes accompanied with mild inflammation (Sylvia A.Price, 2006). In 2019 the incident of osteoarthritis cases at the Siti Khodijah Muhammadiyah Sepanjang Hospital was 6571 patients. Therefore, osteoarthritis is the 3rd common disease after LBP and COPD. Obesity in one of the causes that can increased risk of osteoarthritis. especially those can affect the body’s weight support joints such as the knee. Body mass index calculations are used to classify overweight in adults. To determine is there a corelation between body mass index and severity degree of knee osteoarthritis based on plain radiographs according to the Kellgren-Lawrence grading scale in patients at Siti Khodijah Muhammadiyah Sepanjang Hospital. This study used a cross-sectional design with consecutive sampling technique on 49 knee osteoarthritis patients at Siti Khodijah Muhammadiyah Sepanjang Hospital. The data that used in this study is patient’s medical record. From the severity of osteoarthritis in 49 respondents, the results were grade I as much as 13 (26,5%), grade II as much as 11 (22, 4%), grade III as much as 14 (28, 6%), and grade IV as much as 11(22, 4%) respondents. Whereas on the body mass index, the results were thin (≤17,0-18,4) as much as 2 (4,1%), normal (18,5-25,0) as much as 24 (49%), obesity (25,1-27,0) as much as 12 (24,5%), and severe obesity (>27,0) as much as 11 (22,4%) respondents. The result of statistical test using the Spearman test obtained a significance value (p): 0.578 (p>0.05). There is no significant relationship between bodymass index and the severity degree of knee osteoarthritis based on plain radiographsaccording to the Kellgren-Lawrence grading scale at the Siti Khodijah MuhammadiyahSepanjang Hospital.Keywords : Knee osteoarthritis, severity degree of knee osteoarthritis, body mass index.